Association of low serum 25-hydroxyvitamin D levels with hearing loss severity in Meniere disease: a cross-sectional study - Wu, Yunqin; Lai, Zhenzhen; Li, Ange; Han, Weiwei; Liu, Xiaoxia; Fan, Weinv (Frontiers in Neurology, 2025)
IntroductionGrowing evidence implicates vitamin D in inner ear homeostasis, though its association with Ménière’s disease (MD) remains incompletely characterized. This study aimed to compare serum 25-hydroxyvitamin D (25(OH)D) levels between patients with MD and healthy controls and to assess its correlation with hearing thresholds in MD cohort.MethodsIn this cross-sectional study, 49 patients with MD and 250 matched healthy controls were enrolled at our institution between January 2023 and January 2025. Groups were matched for demographics, comorbidities, exercise habits, and seasonal blood collection timing. Serum 25(OH)D levels and pure-tone audiometry (PTA) results were measured and analyzed.ResultsPatients with MD exhibited significantly lower 25(OH)D levels than controls [18.4 ± 5.9 (45.9 ± 14.7 nmol/L) vs. 21.1 ± 6.2 ng/mL (52.7 ± 15.5 nmol/L); p = 0.006]. After adjusting for covariates, vitamin D deficiency was independently associated with MD (adjusted OR = 2.21; 95% CI: 1.13–4.32; p = 0.021). A moderate inverse correlation existed between 25(OH)D and PTA thresholds (ρ = −0.440, p = 0.002).ConclusionHypovitaminosis D is associated with MD and hearing loss severity, warranting further longitudinal studies to explore causality and therapeutic implications.